Feedback driven message spreading on network. (August 2021) - Nian, Fuzhong; Liu, Jinshuo
Highlights: A feedback-driven model of message propagation based on the classical SIR model is proposed. The feedback mechanism affects the structure of the social network, making the network nodes more closely connected. The level of trust between strangers is one of the most important factors affecting the spread of messages. Abstract: This paper focuses on the role of feedback mechanism on message propagation. In this paper, we study the effect of feedback on message propagation in terms of both the motivation of the communicator to propagate the message and the trust of the message recipient in the communicator, and we design a decay mechanism of motivation based on Newton's cooling law. Based on these considerations, we propose a model of message propagation based on the feedback mechanism. We verify the effect of feedback on message propagation by performing numerical simulations in the Watts-Strogatz (WS) and Barabasi-Albert (BA) networks. The simulation results show that the feedback mechanism leads to faster and more persistent message propagation and that the degree of influence on message propagation varies across different network structures. The simulation also results show that the feedback mechanism changes the structure of the social network and makes the nodes between the networks more closely connected.